Application of Atmospheric Pressure Argon Plasma Jet (APAPJ) in Biomedical Science and Engineering - Jyoti Prakash Gurung; Deepak Prasad Subedi; Rajendra Shrestha; Bhupal Govinda Shrestha (Journal of Tropical Life Science, 2020)
In this paper, we demonstrated the application of atmospheric pressure argon plasma jet (APAPJ) in biomedical science such as cancer therapy and biomedical engineering such as surface modification of polystyrene Petri dishes for animal cell culture. We observed that APAPJ, when exposed to breast cancer cell line (MDA-MB-231) for 60 seconds at a distance of ~ 2.5 cm, reduced the cancer cells by 57%. This reduction in cancer cell concentration demonstrated the cancer-killing property of APAPJ. Further optimization of APAPJ's various operational parameters and in-depth biochemical study is required to figure out the mechanism responsible for killing cancer cells. Also, we investigated cell adhesion and proliferation due to APAPJ treatment by Crystal Violet (CV) staining and MTT Assay. We observed that APAPJ treatment of polystyrene Petri dishes for 60 - 240 s at a distance of ~ 3.5 cm exhibited enhancement in adhesion of breast cancer cell line (MDA-MB-231). We also demonstrated the increase in hydrophilicity by a reduction in contact angle to 30.3Â°Â±3 after 240 seconds of APAPJ treatment of polystyrene samples. The hydrophilicity of the substrate has proven to enhance cell adhesion. Consequently, APAPJ could be employed as a simple, inexpensive and environmentally friendly method for surface modification of polystyrene plates for animal cell culture.